Разрушение транспортным током сверхпроводимости неоднородной пленки в смешанном состоянии - Безуглый, А.И. (Физика низких температур, 2000)
Рассмотрено разрушение транспортным током сверхпроводимости широкой пленки в перпендикулярном магнитном поле, происходящее при конкуренции двух механизмов - роста нормального домена (ND) и неустойчивости вязкого течения магнитного потока. В условиях доминирования первого механизма анализ стационарных доменных состояний позволяет систематизировать все типы вольтамперных характеристик (ВАХ) пленки с локальной неоднородностью и найти зависимость тока SN-перехода от величины магнитного поля B и температуры среды T₀. Показано, что дополнительный разогрев пленки с ND, возникающий вследствие диссипативного движения вихрей в S-области, может приводить к исчезновению гистерезиса ВАХ при увеличении B или T₀. С использованием известных результатов для тока неустойчивости течения магнитного потока получена полевая зависимость температуры кроссовера между рассмотренными механизмами разрушения сверхпроводимости. Основные теоретические результаты сравниваются с экспериментом. The destruction of superconductivity by the transport current is investigated for the case of a wide film in a perpendicular magnetic field. The destruction of superconductivity occurs by two competing mechanisms: growth of a normal domain (ND), and instability of the viscous flow of the magnetic flux. Under conditions in which the first mechanism is dominant, analysis of the stationary domain states permits one to systematize all of the different types of current–voltage (IV) characteristics of a film with a local inhomogeneity and to find the dependence of the SN junction current from the values of the magnetic field B and the temperature T₀ of the medium. It is shown that additional heating of a film with a ND on account of the dissipative motion of vortices in the S region can lead to vanishing of the hysteresis of the IV characteristic as B or T₀ is increased. The known results on the current at which the magnetic flux flow becomes unstable are used to obtain the field dependence of the crossover temperature of these two mechanisms for the destruction of superconductivity. The main theoretical results are compared with experiment.